MicroRNA‐204‐5p Deficiency within the vmPFC Region Contributes to Neuroinflammation and Behavioral Disorders via the JAK2/STAT3 Signaling Pathway in Rats - Xiao Chen; Yeting Gan; Kaiqi Zhang; Yuhan Wu; Ye Li; Tian Lan; Xianghua Zhuang; Shihong Chen; Shuyan Yu (Advanced Science)
Abstract Major depressive disorder (MDD) is usually considered associate with immune inflammation and synaptic injury within specific brain regions. However, the molecular mechanisms underlying the neural deterioration resulting in depression remain unclear. Here, it is found that miR‐204‐5p is markedly downregulated in the ventromedial prefrontal cortex (vmPFC) in a chronic unpredictable mild stress (CUMS) induce rat model of depression. Knockdown of miR‐204‐5p in the vmPFC of normal rats results in depression and anxiety‐like behaviors accompanied with the activation of microglia, elevated levels of pro‐inflammatory cytokines, and increased numbers of neural apoptotic cells, effects which appear to be mediated by activation of the JAK2/STAT3 signaling pathway. Electrophysiological recordings further demonstrate that knockdown of miR‐204‐5p induces abnormal excitability of pyramidal neurons. In contrast, upregulation of miR‐204‐5p in the vmPFC of CUMS rats significantly causes inhibition of JAK2/STAT3 signaling pathway, improvements in neuronal impairments, and an abolition of the depression and anxiety‐like behaviors. Moreover, pharmacological blocking of the JAK2/STAT3 signaling pathway significantly ameliorates abnormal behaviors resulting from miR‐204‐5p deficiency within the vmPFC. Collectively, these results provide robust evidence that the miR‐204‐5p/JAK2/STAT3 pathway may critically involve in the pathogenesis of depression, which may serve as potentially critical therapeutic target in the treatment of MDD.